Sosialisasi Etika Bisnis untuk Manajemen Usaha Pelaku UMKM Istiqomah di Kelurahan Oimbo - Kartin Aprianti; Alief Sofyan Lanang; Molita Molita; Yuliani Fitari; Muhammad Nur Haryadin (Jurnal Nusantara Berbakti, 2025)
The conduct of business,whether on a large or small scale,is faced with significant ethical issues.Business ethics refer to the moral  principles that must be upheld by business practitioners.this community service activity (PKM) focuses on MSMEs in the food industry,particularly cake businesses,in  oimbo village.the aim of this activity is to provide an understanding of the business ethics necessary for running a business,especially in densely populated areas. The method offered to partners/MSMEs is in the form of education/socialization using LEAFLETs which are carried out door to door. The material provided in the leaflet includes discussions on (1) The Role of Ethics in Business for MSMEs, (2) Benefits of doing business for MSMEs (3) Application of ethical principles in business in financial, marketing, production and HR activities. The results of the activity showed that partners were very enthusiastic in listening and discussing during the activity. In addition, it can provide knowledge about ethics in running a business.